Suggestive Communication with the Ventilated Patient (European Journal of Mental Health, 2007)
Mechanical ventilation (MV) is a life saving method usually applied in the Intensive Care Units (ICU) for patients in a critical condition. Today it is more and more obvious that patients treated in the ICU require not only intensive physical (medical) care, but also intensive psychological support in order to avoid severe stress and to cope with the situation. They need help to understand the aim and helpfulness of the treatment, and information about the peculiar or frightening aspects of the situation, in order to promote positive processing. In this paper we summarise an approach, called psychological support based on positive suggestions (PSBPS), where patients on MV were supported with suggestions based on the principles of hypnotic communication. We present the foci of the phases of (1) initiation, (2) maintenance and (3) weaning off from MV from a psychological point of view, along with some verbatim suggestions we used with patients during these three completely different phases of MV. The main results of a randomised prospective study testing the effectiveness of PSBPS are presented briefly.